The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1152/ajpcell.00077.2014
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between human ClC-2 and CFTR Cl channels with pharmacological agents

Abstract: It has been difficult to separate/identify the roles of ClC-2 and CFTR in Cl(-) transport studies. Using pharmacological agents, we aimed to differentiate functionally between ClC-2 and CFTR Cl(-) channel currents. Effects of CFTR inhibitor 172 (CFTRinh172), N-(4-methylphenylsulfonyl)-N'-(4-trifluoromethylphenyl)urea (DASU-02), and methadone were examined by whole cell patch clamp on Cl(-) currents in recombinant human ClC-2/human embryonic kidney 293 (ClC-2/HEK293) cells stably transformed with Epstein-Barr n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…In addition, ClC-2 knockdown T84 cells did not respond to lubiprostone whereas CFTR knockdown T84 cells had significantly increased Cl ¡ current in response to lubiprostone ( Table 2). 9,98,102,111,112,[114][115][116][117][118][119][120][121][122][123][124][125][126] Collectively, these findings indicate that lubiprostone selectively stimulates ClC-2 Cl ¡ currents in intestinal epithelial cells at low doses. However, there are several alternate mechanisms of action of lubiprostone revealed by recent studies including ion transporter trafficking, mucus release, and smooth muscle contraction.…”
Section: Pharmaceutical Targeting Of Clc-2mentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, ClC-2 knockdown T84 cells did not respond to lubiprostone whereas CFTR knockdown T84 cells had significantly increased Cl ¡ current in response to lubiprostone ( Table 2). 9,98,102,111,112,[114][115][116][117][118][119][120][121][122][123][124][125][126] Collectively, these findings indicate that lubiprostone selectively stimulates ClC-2 Cl ¡ currents in intestinal epithelial cells at low doses. However, there are several alternate mechanisms of action of lubiprostone revealed by recent studies including ion transporter trafficking, mucus release, and smooth muscle contraction.…”
Section: Pharmaceutical Targeting Of Clc-2mentioning
confidence: 75%
“…[111][112][113] However, a recent study has shown that CFTR ihn 172 also inhibits ClC-2 Cl ¡ currents. 114 Other laboratories have detected dual activation of CFTR and ClC-2 in a dose-dependent manner. However, this may relate to dosedependent effects of lubiprostone, which when used at dosages 10-fold higher that those required to activate ClC-2 can stimulate CFTR Cl ¡ currents.…”
Section: Pharmaceutical Targeting Of Clc-2mentioning
confidence: 98%
“…Drugs approved for OIC (Table 1) Lubiprostone Lubiprostone is a bicyclic fatty acid derived from prostaglandin E1 (PGE1) metabolite which increases fluid secretion in the gastrointestinal tract [Cuppoletti et al 2004[Cuppoletti et al , 2014 by stimulating the cystic fibrosis transmembrane regulator and type 2 chloride channels (ClC2) in the apical membrane to secrete chloride and water into the lumen [Bijvelds et al 2009;Schiffhauer et al 2013]. This results in increased peristalsis, laxation, and acceleration of small intestinal and colonic transit [Camilleri et al 2006].…”
Section: Barriers To Diagnosis Of Oicmentioning
confidence: 99%
“…Previous studies have shown that ClC-2 is also regulated by hormones (8991), drugs (92–100), proteins (101107), kinases (108114), transcription factors (115,116), inhibitors (117–120), scorpion venom (121), α1-adrenoceptor (122), Plasmodium berghei (123), adenosine triphosphate (124,125), ClH 3 (40,126137), permeant anions (138,139), membrane cholesterol (140) and the tyrosine endocytosis motif (141). …”
Section: Functional Properties Of Clc-2mentioning
confidence: 99%